2017
DOI: 10.21927/jnki.2017.5(1).68-75
|View full text |Cite
|
Sign up to set email alerts
|

Faktor-Faktor yang Berhubungan dengan Pernikahan Dini pada Wanita

Abstract: Abstrak 's education (p=0.290), parents' income (p=0.356) and respondents' religiosity (p=0.489). The result of logistic regression analysis showed that respondents' income was the most dominant factor affecting early marriage in women. Conclusion the most significant factor related to early marriage was respondents' income.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
16

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 2 publications
0
7
0
16
Order By: Relevance
“…Various studies have shown that economic factors significantly inform parents' decision to have their children marry early. 16 Parents Sastro Mustapa Wantu, et.al. DOI: 10.22373/sjhk.v5i2.9573 http://jurnal.arraniry.ac.id/index.php/samarah with more children are more likely to quickly marry their children off, as this reduces the financial burden they must bear.…”
Section: Underage Marriage In the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have shown that economic factors significantly inform parents' decision to have their children marry early. 16 Parents Sastro Mustapa Wantu, et.al. DOI: 10.22373/sjhk.v5i2.9573 http://jurnal.arraniry.ac.id/index.php/samarah with more children are more likely to quickly marry their children off, as this reduces the financial burden they must bear.…”
Section: Underage Marriage In the Literaturementioning
confidence: 99%
“…33 Women who marry at a young age are also more at risk for having an abortion, which adversely affects their fertility. 34 ICRW 35 reveals that underage mothers (aged [15][16][17][18][19] are twice as likely of dying from pregnancy-related complications. Nour 36 reports that women who marry at a young age are more vulnerable to sexually transmitted diseases, cervical cancer, and malaria.…”
Section: Underage Marriage In the Literaturementioning
confidence: 99%
“…Hasil uji statistik menunjukkan bahwa terdapat hubungan yang signifikan antara pendapatan orang tua dengan pernikahan usia dini dengan nilai p value = 0,037 (p˂0,05) (Nasution, 2021). Namun penelitian ini tidak sejalan dengan penelitian yang dilakukan oleh Wulanuari (2017) bahwa tidak ada hubungan antara pendapatan orang tua dengan pernikahan dini pada wanita dengan nilai p value = 0,356 (p˃0,05) (Wulanuari & A, 2017). Hal yang mempengaruhi remaja untuk melakukan perkawinan usia dini karena keadaan keluarga yang hidup dibawah garis kemiskinan dan membuat remaja untuk segera menikah di usia muda karena dianggap dapat meringankan beban kedua orang tuanya.…”
Section: Nounclassified
“…(Budiman & Riyanto, 2013;Sangging, Setyowati, & Mardiyaningsih, 2014;Zain & Zain, 2017) Beberapa studi sebelumnya menunjukkan bahwa tingkat pendidikan yang rendah berhubungan dengan kecenderungan dalam melakukan pernikahan dini. (Maliana, 2017;Sah et al, 2014;Sari & Saragih, 2018;Wulanuari, Anggraini, & Suparman, 2017;Yüksel-Kaptanoğlu & Ergöçmen, 2014;Zain & Zain, 2017) Seseorang yang pendidikannya rendah lebih berpeluang untuk menikah dini yaitu sebesar 0.463 kali dibandingkan dengan yang pendidikan tinggi. (Idawati, 2018) Hal tersebut disebabkan karena pola pikir yang sempit, sehingga dalam pengambilan keputusan tidak disertai dengan pertimbangan yang matang mengenai dampak dan akibat dari menikah dini.…”
Section: Pengolahan Dan Analisis Dataunclassified